1992
DOI: 10.1111/j.1600-0765.1992.tb01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated lymphocyte subsets in adult periodontitis*

Abstract: The activation state of T and B lymphocytes in the peripheral blood of periodontitis patients may be a reflection of disease activity. We have utilized 2- and 3-color flow cytometric analyses using a new chromophore, peridinin chlorophyll A protein, and conventional dyes, fluorescein isothiocyanate and phycoerythrin, conjugated to monoclonal antibodies against activated lymphocyte surface markers to measure blood lymphocyte subsets from 18 periodontitis patients and 16 periodontally healthy control subjects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 45 publications
2
44
3
Order By: Relevance
“…If juvenile periodontitis (IP) and rapidly progressive periopresent, an elevated CD4:CD8 ratio may be attributable dontitis (RPP) (Kinane et al, 1989), others have found this to a decrease in the number of CD8+ cells (Nagasawa et ratio to be elevated relative to healthy controls (Katz et al, 1995;Takahashi etal., 1995), although again this is not a consistent finding (Celenligil et al, 1990a;Afar et al, 1992). The conflicting results from these studies may be due to the large variability of the values within patient groups (Katz et al, 1988;Takahashi et al, 1995 (Mahanonda et al, 1989(Mahanonda et al, , 1991.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphocontrasting
confidence: 45%
See 3 more Smart Citations
“…If juvenile periodontitis (IP) and rapidly progressive periopresent, an elevated CD4:CD8 ratio may be attributable dontitis (RPP) (Kinane et al, 1989), others have found this to a decrease in the number of CD8+ cells (Nagasawa et ratio to be elevated relative to healthy controls (Katz et al, 1995;Takahashi etal., 1995), although again this is not a consistent finding (Celenligil et al, 1990a;Afar et al, 1992). The conflicting results from these studies may be due to the large variability of the values within patient groups (Katz et al, 1988;Takahashi et al, 1995 (Mahanonda et al, 1989(Mahanonda et al, , 1991.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphocontrasting
confidence: 45%
“…Surface lipopolysaccharides from Gram-negative periodontal bacteria appear to provide the major activation signal for NK-cell-mediated cytotoxicity (Lindemann, 1988 CD45RO and CD45RA expression is seen on approximately 60% and 40%, respectively, of CD4+ cells in the peripheral blood of periodontally healthy subjects (Gemmell et al, 1992). Overall, the numbers of nafve and memory cells in peripheral blood appear to be similar in patients with adult chronic periodontitis and healthy controls (Afar et al, 1992). The frequency of memory Tcells (CD4+ CD45RO+), however, is significantly elevated in these patients.…”
Section: A) Proliferative Responses Of Peripheral Blood (Pb) T-lymphomentioning
confidence: 86%
See 2 more Smart Citations
“…Host immune responses have been suggested to play a key role in periodontal diseases [1,2]. T and B lymphocytes appear to be prominent in chronic periodontal lesions in humans [3,4]. Th2 cells have been focused on the etiology of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%